Corrosion inhibitor in CO2-O2-containing environment: Inhibition effect and mechanisms of Bis(2-ehylhexyl) phosphate for the corrosion of carbon steel. (February 2021) - Hu, Junying; Xiong, Qi; Chen, Longjun; Zhang, Chenfeng; Zheng, Ziqi; Geng, Shuai; Yang, Zhi; Zhong, Xiankang
Highlights: BEP can effectively protect carbon steel from corrosion in CO2 –O2 –containing environment. BEP anion is much easier to adsorb on iron surface than O2 . Inhibition layer binds with steel surface via P–O–Fe bond and P–Fe bond. Abstract: The corrosion inhibition of carbon steel in CO2 -O2 -containing environment is one of the biggest challenges in flue gas injection for enhanced oil recovery. Herein we report the possibility to use Bis(2-ehylhexyl) phosphate (BEP) to inhibit the corrosion in CO2 -O2 -containing solution and simultaneously the inhibition mechanisms are unmasked. The results show that the corrosion is greatly inhibited with 500 ppm BEP in 1 wt% NaCl solution with 0.02 MPa CO2 and 3 mg/L O2 . BEP could interact with Fe and corrosion products via the formation of P-O-Fe bond and P-Fe bond to generate a barrier layer, thus, offering a protective performance.